Arabic language teaching evaluation process for non-native speakers - Taqi Eddin M. Abdelbaset; Nidal A.M Jabari (International Journal of Education and Learning, 2020)
Teaching languages in general and teaching Arabic to non-native speakers, in particular, have had two attempts to create a standardized test to assess language proficiency in Arabic for non-native speakers. This research is a comparative and descriptive study of the reality of the achievement tests carried out by An-Najah National University in Palestine at the College of Arts, Department of Arabic Language Teaching Non-Native Speakers, as it has been the leading educational institution established in the State of Palestine for decades. The need for courses on preparing the correct tests for students comes through seminars or conferences or a direct meeting between the teacher and the authors of questions for the Arabic language test for speakers of other languages. The preparation of the exam requires a specific skill and knowledge of the circumstances of the learners and the variations between them so that questions can be with a challenging level with a low percentage, middle-level questions, and they are the most and simple questions to answer directly, these questions can be at the beginning of the exam to give a boost to the student who takes the exam.